Systematic optimization of prime editing for enhanced efficiency and versatility in genome engineering across diverse cell types - Mu, Huiling; Liu, Yeyi; Chi, Yijia; Wang, Fei; Meng, Shuting; Zhang, Yi; Wang, Xunting; Zhao, Dongxin (Frontiers in Cell and Developmental Biology, 2025)
Prime editing offers remarkable versatility in genome editing, but its efficiency remains a major bottleneck. While continuous optimization of the prime editing enzymes and guide RNAs (pegRNAs) has improved editing outcomes, the method of delivery also plays a crucial role in overall performance. To maximize prime editing efficiency, we implemented a series of systematic optimizations, achieving up to 80% editing efficiency across multiple loci and cell lines. Beyond integrating the latest advancements in prime editing, our approach combined stable genomic integration of prime editors via the piggyBac transposon system, selection of integrated single clones, the use of an enhanced promoter, and lentiviral delivery of pegRNAs, ensuring robust, ubiquitous, and sustained expression of both prime editors and pegRNAs. To further assess its efficacy in challenging cell types, we validated our optimized system in human pluripotent stem cells (hPSCs) in both primed and naïve states, achieving substantial editing efficiencies of up to 50%. Collectively, our optimized prime editing strategy provides a highly efficient and versatile framework for genome engineering in vitro, serving as a roadmap for refining prime editing technologies and expanding their applications in genetic research and therapeutic development.